VD_FINDINFO HC / 2010 / 118 vom 14. Januar 2010 - VD Tribunal cantonal (2010)
LIQUIDATION DU RÉGIME MATRIMONIAL, RÉGIME MATRIMONIAL, OBLIGATION D'ENTRETIEN | 122 CC, 125 CC, 142 CC, 145 al. 1 CC, 209 CC, 218 CC, 265 CPC, 267 CPC, 3 CPC, 373 al. 2 CPC, 373 CPC